2012 International Conference on Privacy, Security, Risk and Trust and 2012 International Confernece on Social Computing 2012
DOI: 10.1109/socialcom-passat.2012.49
|View full text |Cite
|
Sign up to set email alerts
|

On the Predictability of Human Contacts: Influence Factors and the Strength of Stronger Ties

Abstract: Abstract-While the analysis of online social networks is a prominent research topic, offline real-world networks are still not covered extensively. However, their analysis can provide important insights into human behavior. In this paper, we analyze influence factors for link prediction in human contact networks. Specifically, we consider the prediction of new links, and extend it to the analysis of recurring links. Furthermore, we consider the impact of stronger ties for the prediction. The results and insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 35 publications
(66 reference statements)
4
43
0
Order By: Relevance
“…In [7], we showed that the predictability of new links can be further improved by data from online networks, proposing a new unsupervised link prediction method that combines the information of different networks. In [17] Tsugawa and Ohsaki also analysed the quality of unsupervised methods in the context of link prediction in face-toface proximity networks; they compared the predictability of links in face-to-face contact networks and other types of social networks, supporting our earlier work in [15]. …”
Section: Related Worksupporting
confidence: 55%
See 1 more Smart Citation
“…In [7], we showed that the predictability of new links can be further improved by data from online networks, proposing a new unsupervised link prediction method that combines the information of different networks. In [17] Tsugawa and Ohsaki also analysed the quality of unsupervised methods in the context of link prediction in face-toface proximity networks; they compared the predictability of links in face-to-face contact networks and other types of social networks, supporting our earlier work in [15]. …”
Section: Related Worksupporting
confidence: 55%
“…[4], which we also applied for the data analysed in this work. In [15], we presented a first analysis concerning the predictability of new and recurring links in real world face-to-face contact networks. In [7], we showed that the predictability of new links can be further improved by data from online networks, proposing a new unsupervised link prediction method that combines the information of different networks.…”
Section: Related Workmentioning
confidence: 99%
“…The connection between research interests, roles and academic jobs of conference attendees is further analyzed in Macek et al (2012). Furthermore, the predictability of links in face-to-face contact networks and additional factors also including online networks has been analyzed by Scholz et al (2012Scholz et al ( , 2013. ).…”
Section: Observing Encounters and Activitiesmentioning
confidence: 99%
“…In the following, we specifi cally consider human contact networks obtained using the Conferator system, and summarize results concerning the analysis of contacts patterns in those social networks, and their underlying mechanisms (cf. Scholz et al 2012 ). Homophily (Rosvall and Bergstrom 2007 ), for example, is a classic topic of social network analysis.…”
Section: Characterizing Roles and Linksmentioning
confidence: 99%
“…Table 4.2 shows exemplary results (cf. Scholz et al 2012 ) of a descriptive link prediction analysis at the Hypertext 2011 conference in the form of characteristic patterns (Atzmueller et al 2009 ;Atzmueller and Puppe 2008 ) that describe certain subgroups of the conference participants. The table shows combinations of infl uence/role factors that are signifi cantly correlated with the duration of recurring contacts at the conference.…”
Section: Characterizing Roles and Linksmentioning
confidence: 99%